Pelatihan Elektropneumatic Untuk Guru Produktif Teknik Elektronika di SMK Negeri 2 Makassar - Wahrini, Retyana; Hasbi, Hasbi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The main problem of this activity is based on the results of observations and discussions with electronics engineering teachers at SMK Negeri 2 Makassar. The problems faced in developing the competence possessed by teachers are due to the limited availability of special electropneumatic practicum equipment. This causes school difficulties in the process of implementing electropneumatic practicum learning activities due to the low competence of teachers in the field of electropneumatics. Therefore, training was conducted for productive teachers majoring in electronics engineering at SMK Negeri 2 Makassar so that teachers could develop their competence in the field of electropneumatics. The results achieved are that after this training, the teacher can understand the basic components of electropneumatics, apply Fluidim for simulation, be able to assemble electropneumatic control systems, be able to use various types of electropneumatic directional valves, be able to understand the application of various electropneumatic actuators, and be able to design operational sequences of control systems electropneumatic.